2014
DOI: 10.1182/blood.v124.21.3791.3791
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of a Pair of Concordant Twins with Infant ALL and Discordant Clinical Outcome Reveals Immunoescape As a Mechanism of Disease Persistence in MLL-Rearranged Leukemia

Abstract: MLL-fusion is the most common genetic abnormality in acute lymphoblastic leukemia (ALL) of infancy and occurs in approximately 80% of the cases. Infant ALL represents a biologically distinctive entity with a highly immature pro-B immunophenotype associated with a particularly unfavorable prognosis due to a high proportion of early relapses. This may be due to the survival of dormant residual disease protected by the bone marrow niche. We have characterized a pair of monozygotic twin sisters diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The first one was reported by Henning Fedders et al in 2014. In their study, it was suggested that twin cells, with relapse, might evade immune surveillance as a mechanism of disease persistence [26].…”
Section: Discussionmentioning
confidence: 99%
“…The first one was reported by Henning Fedders et al in 2014. In their study, it was suggested that twin cells, with relapse, might evade immune surveillance as a mechanism of disease persistence [26].…”
Section: Discussionmentioning
confidence: 99%